Modelo De Intervención Urbana En La Franja De Adecuación De La E.E.P Los Cerros Orientales Con Relación Al Borde Urbano En El Sector De La Mariposa. (2022)
The city of Bogotá is made up of a spectacular border: the Cerros Orientales Forest Reserve. However, its high level of degradation and ecosystem deterioration demands the development of social inclusion initiatives for the recovery of its forests.Within the reserve, human activities carried out in the Cerros Orientales de Bogotá produce different impacts on its physical, biological and sociocultural components.